Effects of respiratory flora regulation on microbial environment and IL-10/STAT3 signaling pathway in the bronchiolitis obliterans after lung transplantation: Respiratory flora and bronchiolitis obliterans - Wang, Xin; Liu, Tianhua; Chen, Yizhuo; Xu, Ziqing; Zhan, Jianghua; Dong, Ming (Cellular and Molecular Biology, 2023)
Our purpose of this study was to explore the application effect of respiratory flora regulation in bronchiolitis obliterans after lung transplantation, and its regulatory effect on the microbial environment of the lesion and the IL-10/STAT3 signaling pathway. 25 clean-grade C57BL/6 male mice and 5 BALB/c male mice were selected for orthotopic tracheal transplantation and postoperative respiratory flora regulation in a hospital animal room from Jan 2019 to Dec 2021. Next, the changes in the microbial environment and the IL-10/STAT3 signaling pathway before and after respiratory flora regulation were compared, so as to evaluate the regulatory effect of this method. The Simpson index did not show a significant difference before and after respiratory flora regulation intervention (P>0.05). However, the Chao1, ACE, Shannon, and Actinobacteria dominant indices were higher after the intervention. There were significant changes in the abundance of Proteobacteria, Bacteroidetes, Acidobacteria, Firmicutes, Propionibacterium, Corynebacterium, Staphylococcus, and Streptococcus after the intervention (P<0.05). Additionally, IL-10 and STAT3 levels were higher after the intervention and showed significant differences (P<0.05) compared to before. Regulating the respiratory tract flora can improve the microbial environment of bronchiolitis obliterans post-lung transplantation. This helps balance the respiratory flora, increase IL-10 and STAT3 levels, and aid in the recovery of inflammatory responses.